STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN FURNITURE PADA CV. PELITA JAYA PADANG - Rahayu, Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
The aim of this research is to identify what factors that caused declining in sales volume in CV.Pelita Jaya Padang. Beside that , this research also examines what strategies that have been carried out and some alternative strategies should have been implemented to encounter competitors. This research is undertaken in CV.Pelita Jaya Padang where Chairman and Empoyees are key informants. Data is obtained by interviewing key informants and observing the company directly. The result of this research reveals that some strategies have been implemented gradually by company.The company has assessed competitive price in all type of products. On the other hand , the company has improved the quality of the products and has performed marketing strategy policies slightly.